Pelvic floor muscle training during the childbirth period: a best practice implementation project - Israel, Janet; Bennett, Clare; Carrier, Judith; Darbhamulla, Anna; Wolujewicz, Sarah; Klugarová, Jitka; Klugar, Miloslav (JBI evidence implementation, 2025)
INTRODUCTION: In the UK, the Royal College of Midwives and the Chartered Society for Physiotherapy advocate that women undertake early and effective pelvic floor muscle training (PFMT) during the childbirth period to reduce the incidence of urinary incontinence (UI). OBJECTIVES: This project sought to assess and improve midwives' compliance with best practice recommendations for PFMT in a UK NHS maternity service, with the goal of improving PFMT for women. METHODS: This project used the JBI Evidence Implementation Framework and JBI's best practice recommendations for PFMT. Following a baseline audit of midwives' practice, the results were considered. The JBI Getting Research into Practice (GRiP) approach was used to identify barriers and facilitators to improve compliance with recommendations. A follow-up audit was undertaken after the development of a revised continuing professional development (CPD) program for midwives on PFMT. RESULTS: The results showed improved compliance with all four audit criteria. Criterion 1 (midwives' engagement with PFMT) increased from 76% to 92%; Criterion 2 (PFMT during the antenatal period) rose from 50% to 92%; Criterion 3 (postnatal risk assessment for UI) rose from 45% to 67%; and Criterion 4 (PFMT for high-risk women during the postnatal period) increased from 49% to 92%. CONCLUSION: Whilst this study presented some challenges in implementing evidence-based initiatives in a UK NHS maternity service, it also demonstrated that an audit approach can overcome these, thereby improving compliance with best practices. In this case, changes to a CPD PFMT program increased midwives' compliance with evidence-based practice criteria. In the future, when implementing change in the NHS system, consideration should be given to organizational and leadership factors. Further audits will need to be carried out to monitor practice and effect change. SPANISH ABSTRACT: http://links.lww.com/IJEBH/A322.
Keywords: Pregnancy; Humans; státní lékařství; Guideline Adherence; porod; Midwifery; Female; pánevní dno; Exercise Therapy; babictví; Evidence-Based Practice; Spojené království; lidé; inkontinence moči; United Kingdom; Parturition; Urinary Incontinence; Pelvic Floor; ženské pohlaví; dodržování směrnic; Practice Guidelines as Topic; těhotenství; směrnice pro lékařskou praxi jako téma; lékařská praxe založená na důkazech; State Medicine; terapie cvičením